Avaliação pré-clínica da pele da tilápia (Oreochromis niloticus), como curativo biológico oclusivo, no tratamento de queimaduras - Lima Júnior, Edmar Maciel (2017)
In Brazil, about 1 million cases of burns occur per year, of which 100 thousand patients will seek hospital care and 2.500 will die from their injuries. Our country has never had a legally registered animal skin for use in burned patients, although in first world countries, treatment with human or animal skin provided by skin banks is considered a gold standard. The objective of this study was to evaluate the effect of Nile tilapia (Oreochromis niloticus) skin, used as a biological occlusive dressing, in the treatment of burn wounds, through three preclinical studies, developed and published in scientific journals by researchers of the Center of Drug Research and Development (NPDM) of the Federal University of Ceará. The first manuscript was about the characterization of the microflora of the fishes’ oral cavity, skin and subcutaneous tissue. When considering the absence of infectious signs and a load below 100,000 CFU, it is concluded that the CFU values found in this study consisted of normal, non-infectious microflora. In the second manuscript, the NPDM researchers team presented results of a study to characterize the skin of Nile tilapia, based on their physical characteristics (tensile strength), histomorphological and typification of collagen composition. The microscopic characteristics of the tilapia skin were similar to the morphological structure of the human skin, with high resistance and extension to breaking traction, which supports its possible application as biomaterial. The third scientific publication evaluated the use of tilapia skin as an occlusive dressing for superficial and deep second-degree burns in rats to evaluate its in vivo use for the first time. The results showed that the tilapia skin showed good adherence in the wounds induced by burns in the rats, interfering positively in the cicatricial process. In addition, the absence of significantly altered values in laboratory tests signals the safety of skin use as a dressing. The results presented by the researchers enable the continuation of the research for human studies to confirm its safety and efficacy as a biological dressing. The published preclinical studies have demonstrated that tilapia skin has the necessary characteristics and properties to be used safely and effectively, confirming its potential as a biological occlusive dressing for the treatment of burn wounds in humans.